THE IMPACT ON THE PANDEMIC CORONAVIRUS DISEASE 2019 (COVID-19) ON HOUSEHOLD WELFARE IN WEST SUMATERA - Fery Andrianus; Hefrizal Handra; Arie Sukma; Khaira Alfatih (LPPM Universitas Muhammadiyah Sumatera Barat, 2021)
West Sumatera is the province with the highest number of Covid-19 casesin Sumatera Island and nationally it isin the ninth position. Similar to other events at the international and national levels, the spread of Covid-19 in West Sumatera has an impact on the regional economy. It affects not only the growth and other macroeconomic indicators but also the welfare of households and society directly. This study examines the effects of the pandemic Covid-19 on household welfare using objective and subjective indicators and observe into what extent the influence of PSBB and government assistance on community conditions during this pandemic. The results show that firstly, household welfare is above the provincial minimum wage, secondly, PSBB also affects people’s income, and lastly, not all households or communities are informed about the assistance from the government during the pandemic. Keywords: Covid-19, objective and subjective indicators, welfare, provincial minimum